PENERAPAN PEMBELAJARAN FISIKA DENGAN ANALOGI UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMA (UPEJ Unnes Physics Education Journal, 2012)
The material in the abstract physics need an alternative in order to make it easier for students learning to understand it, one of them by analogy. This study aimed to determine: (1) How does the implementation of teaching physics by analogy (2) Is the analogy of learning physics can improve learning outcomes physics and high school students (3) Is the analogy of learning physics is more effective than conventional learning. The research data in the form of observations during the learning process and learning outcomes ongoing cognitive obtained obtained from the test. Based on test results obtained gains that increase student learning outcomes on the criterion of 0.60 was the level of mastery learning reaches 90%. While based on t-test analysis showed no significant difference between learning by analogy and learning physics conventional physics